Flexitarian Diets and Health: A Review of the Evidence-Based Literature - Derbyshire, Emma J. (Frontiers in Nutrition, 2017)
A flexitarian or semi-vegetarian diet is one that is primarily vegetarian with the occasional inclusion of meat or fish. Of late there appears to be an increasing movement towards this practice. There has not been a recent update on these diets from a health perspective. Using the National Centre for Biotechnology Information PubMed database, a search was made for all studies published between 2000 and 2016 that met defined inclusion criteria. A total of 25 studies were located with 12 focusing on body weight and diet quality. There was emerging evidence suggestive of benefits for body weight, improved markers of metabolic health, blood pressure, and reduced risk of type 2 diabetes. Semi-vegetarian diets may also have a role to play in the treatment of Inflammatory Bowel Diseases such as Crohn’s Disease. Given that there is a higher tendency for females to be flexitarian yet males are more likely to overconsume meat, there is a clear need to communicate the potential health benefits of these diets to males.